1987
DOI: 10.1007/bf00177923
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amphetamine on local cerebral metabolism in normal and schizophrenic subjects as determined by positron emission tomography

Abstract: The effects of d-amphetamine (0.5 mg/kg PO) on regional cerebral glucose utilization were measured with Positron Emission Tomography (PET). Subjects included ten chronic schizophrenics and six controls who received amphetamine, and six chronic schizophrenics and nine controls who received placebo or no treatment. Amphetamine decreased glucose metabolism in all regions studied (frontal, temporal, and striatal) in normal and schizophrenic subjects. The metabolic effects of amphetamine were correlated with plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 40 publications
3
42
0
2
Order By: Relevance
“…33 Reduction of cortical CMRglc is a common response to acute administration of drugs of abuse, 34 as observed with opiates, 35 barbiturates, 36 benzodiazepines, 37 cocaine 38 and amphetamine. 39 This commonality is consistent with a classic theory proposing that activity in subcortical emotion circuits alters human consciousness more when cortical inhibition is suppressed. 40 In this view, metabolic effects of intoxication represent release of subcortical regions from cortical inhibition, resulting in heightened emotions.…”
Section: Importance Of Absolute Measuressupporting
confidence: 87%
See 1 more Smart Citation
“…33 Reduction of cortical CMRglc is a common response to acute administration of drugs of abuse, 34 as observed with opiates, 35 barbiturates, 36 benzodiazepines, 37 cocaine 38 and amphetamine. 39 This commonality is consistent with a classic theory proposing that activity in subcortical emotion circuits alters human consciousness more when cortical inhibition is suppressed. 40 In this view, metabolic effects of intoxication represent release of subcortical regions from cortical inhibition, resulting in heightened emotions.…”
Section: Importance Of Absolute Measuressupporting
confidence: 87%
“…A total of 10 regions of interest (ROIs) were selected because of prior demonstrations of functional abnormalities associated with MA abuse: parietal cortex (Brodmann areas (BAs) 1,2,3,5,7,19,39,40), thalamus, dorsal striatum, ventral striatum, medial orbitofrontal cortex (gyrus rectus and medial orbital gyrus; BA 11), lateral orbitofrontal cortex (lateral, posterior orbital and inferior frontal gyri; BAs 47, 11), infragenual ACC (BAs 25, 32), supragenual ACC (BAs 24, 32, 33), insula (BA 13) and amygdala. 1,6,8,9 ROIs were drawn on the structural MR template provided in SPM2, using MEDx Software (Sensor Systems, Sterling, VA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Diminished cortical activity has been described in several studies with both depressant and stimulant drugs of abuse such as benzodiazepines, morphine, amphetamines, and cocaine (Mathew and Wilson 1991;London et al 1990aLondon et al , 1990bWolkin et al 1987) and has been viewed as a correlate of euphoria (London et al 1990a(London et al , 1990bPearlson et al 1993). However, in our studies, both cortical hypometabolism and cerebellar hypermetabolism were not associated with positive, but rather with unpleasant feelings such as anxiety and depression, cognitive disturbances, and general psychopathological signs.…”
Section: Neurometabolic Effects Of the Drugs And Correlations With Psmentioning
confidence: 99%
“…Several studies with other psychotropic substances with both stimulant and sedative properties (cocaine, morphine, benzodiazepines, barbiturates) reported decreased cortical activity (London et al 1990a,b;Mathew and Wilson 1991). Studies on the effects of stimulant amphetamines are inconsistent with reports of decreases, no effects, or increases of glucose metabolism or cerebral blood flow (Wolkin et al 1987;Kahn et al 1989;Metz et al 1991;Devous et al 1995;Ernst et al 1997). A recent study with intravenous d-amphetamine administration reported no global change, but frontal, limbic, subcortical, and cerebellar increases of regional glucose metabolic rates (Ernst et al 1997).…”
mentioning
confidence: 99%
“…PCP administration to rats and ketamine administration to schizophrenic patients increased metabolism in sensory cortices, motor cortex, thalamus, and limbic areas (e.g., Gao et al 1993;Weissman et al 1987;Lahti et al 1995b). D-amphetamine administration to schizophrenic patients decreased metabolism in frontal and temporal cortical areas (e.g., Wolkin et al 1987). It is possible that deficits in the dopamine and glutamate systems may relate to different aspects of symptomatology and metabolic alterations in schizophrenia.…”
mentioning
confidence: 99%